2001
DOI: 10.1055/s-2001-10806
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Methyl 2,3-Anhydro- and 2,3-O-Sulfinylfuranosides from Unprotected Furanosides Using the Mitsunobu Reaction

Abstract: A new two step procedure for the synthesis of methyl 2,3-anhydro-a-D-lyxofuranoside and methyl 2,3-anhydro-b-D-ribofuranoside from D-xylose involving the intramolecular Mitsunobu reaction is presented. Likewise, methyl 2,3-anhydro-a-L-lyxofuranoside is obtained from L-arabinose. Cyclic sulfites with D-ribo configuration, synthetic equivalents of the corresponding anhydrosugars, are prepared in three steps from D-ribose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 6 publications
2
11
2
Order By: Relevance
“…This strong substrate selectivity is not consistent with results obtained by Fischer glycosylation with MeOH . Both yield and anomeric ratios of glycosides formed by our method are dictated by the configuration of the hydroxy groups of d -pentoses deployed.…”
contrasting
confidence: 99%
“…This strong substrate selectivity is not consistent with results obtained by Fischer glycosylation with MeOH . Both yield and anomeric ratios of glycosides formed by our method are dictated by the configuration of the hydroxy groups of d -pentoses deployed.…”
contrasting
confidence: 99%
“…253 Additionally, the β-selectivities observed with the ribose substrate are higher than those attained with the Fischer glycosylation of MeOH. 254,255 …”
Section: 1- Hydroxy Sugar Donorsmentioning
confidence: 99%
“…Comparison of NMR data of 2 between methyl pentofuranosides indicated that the sugar was ribofuranose linked via an α-glycosidic bond. 11 Amphidinin D (2) was treated with Dowex (H + ) in MeOH, and the resulting mixture was esterified with (R)-MTPACl to obtain the tris-(S)-MTPA ester (7a) of a sugar moiety and the (S)-MTPA ester (8a) of an aglycon of 2 (Scheme 2). The 1 H NMR spectra of 7a and 8a were coincident with those of the tris-(S)-MTPA ester of methyl D-ribofuranoside and the (S)-MTPA ester of 1, respectively.…”
mentioning
confidence: 99%
“…Analyses of 2D NMR data revealed that 2 was the 4- O -pentofuranoside of 1 (Figure ). Comparison of NMR data of 2 between methyl pentofuranosides indicated that the sugar was ribofuranose linked via an α-glycosidic bond …”
mentioning
confidence: 99%